A 5 V-class cobalt-free battery cathode with high loading enabled by dry coating. Issue 4 (6th March 2023) - Yao, Weiliang; Chouchane, Mehdi; Li, Weikang; Bai, Shuang; Liu, Zhao; Li, Letian; Chen, Alexander X.; Sayahpour, Baharak; Shimizu, Ryosuke; Raghavendran, Ganesh; Schroeder, Marshall A.; Chen, Yu-Ting; et al.
Abstract : "Thick electrode using high voltage cathode" can be considered, since this research focuses on high voltage cathode materials. Abstract : Transitioning toward more sustainable materials and manufacturing methods will be critical to continue supporting the rapidly expanding market for lithium-ion batteries. Meanwhile, energy storage applications are demanding higher power and energy densities than ever before, with aggressive performance targets like fast charging and greatly extended operating ranges and durations. Due to its high operating voltage and cobalt-free chemistry, the spinel-type LiNi0.5 Mn1.5 O4 (LNMO) cathode material has attracted great interest as one of the few next-generation candidates capable of addressing this combination of challenges. However, severe capacity degradation and poor interphase stability have thus far impeded the practical application of LNMO. In this study, by leveraging a dry electrode coating process, we demonstrate LNMO electrodes with stable full cell operation (up to 68% after 1000 cycles) and ultra-high loading (up to 9.5 mA h cm −2 in half cells). This excellent cycling stability is ascribed to a stable cathode–electrolyte interphase, a highly distributed and interconnected electronic percolation network, and robust mechanical properties. High-quality images collected using plasma focused ion beam scanning electron microscopy (PFIB-SEM) provide additional insight into this behavior, with a complementary 2-D model illustrating how the electronic percolation network in the dry-coated electrodes more efficiently supports homogeneous electrochemical reaction pathways. These results strongly motivate that LNMO with a high voltage cobalt-free cathode chemistry combined with an energy-efficient dry electrode coating process opens up the possibility for sustainable electrode manufacturing using cost-effective and high-energy-density cathode materials.